The next justice : repairing the Supreme Court appointments process - Eisgruber, Christopher L. (Princeton University Press, 2007)
The Supreme Court appointments process is broken, and the timing couldn't be worse--for liberals or conservatives. The Court is just one more solid conservative justice away from an ideological sea change--a hard-right turn on an array of issues that affect every American, from abortion to environmental protection. But neither those who look at this prospect with pleasure nor those who view it with horror will be able to make informed judgments about the next nominee to the Court--unless the appointments process is fixed now. In The Next Justice, Christopher Eisgruber boldly proposes a way to.